Remittance in Nepalese Economy: Trends, Contributions, and Policy Implications - Adhikari, Hemant Raj; Khatri, Bishnu Bahadur (Patan Pragya, 2024)
Remittances are a major source of foreign income for developing countries such as Nepal. Remittance occupies nearly one fourth of national GDP. It has been a dominant source of foreign currency for the last decades. In this connection, the aim of this research paper is to examinethe current trends and contribution of remittance in Nepalese economy. This is a review-based research paper having descriptive research design. Secondary data are used to accumulate the information and describe the result depending on the research objective. The result revealed that the contribution of remittance to GDP is high in Nepal among South Asian countries. Remittance and GDP revealed a positive relationship. Largely remittance is utilized to meet consumption needs rather than investing in productive sectors. Government should provide a favorable environment in addition to suitable policy for investing remittance money in productive sector for long term economic sustainability.